Modelling the crowding effect of foreign direct investment on domestic investment: evidence from 38 Asian countries / Nurul Azwanie Budang - Budang, Nurul Azwanie (2020)
This study assesses the extent to which Foreign Direct Investment (FDI) in Asia crowds in or crowds out Domestic Investment (DI) in different time period consist of before, during and after Asia and Global financial crises. The data collected are over the period of 1993-2016 and separated into six sub-periods; 1993-1995 (Before Asia Financial Crisis), 1996-1998 (During Asia Financial Crisis), 1999-2001 (After Asia Financial Crisis), 2004-2006 (Before Global Financial Crisis), 2007-2009 (During Global Financial Crisis) and 2010-2016 (After Global Financial Crisis). The model is run for 38 of Asian countries. In this study, researcher estimated the data using Panel Ordinary Least Square (POLS), Fixed Effects (FE), Random Effects (RE), Instrumental Variables (IV) and Fixed Effects with the Discroll and Kraay standard error estimator. Besides that, panel co-integration (Kao residual co-integration and Westerlund) tests and crowding effects formula have been applied to investigate long term relationship. The general empirical finding found that FDI has significantly negative and crowd out effect on DI during and after Asia financial crisis and before and during Global financial crisis. It is supported by the result of panel co-integration tests and long-term formula of crowding effect where the result revealed significantly negative and crowd out effect of FDI on DI in long term period for both of Asia and global financial crisis. For the case of insignificant results before Asia financial crisis and after Global financial crisis, the countries may focus on improvement of DI instead of attracting more FDI. However, FDIs activities keep on moving and aim to help in improvement of DI though it is not significant in host Asia. Thus, this study concluded that implementation of FDI during the crisis may contribute to the improvement of economic growth but discourage the local investor to invest in a country as it was crowded out local investment.